IMPLEMENTASI KURIKULUM BERBASIS CINTA DALAM MENCAPAI PENDIDIKAN HUMANIS DAN BERKEADABAN DI MTsN 2 EMPAT LAWANG - Sri Uswatun Hasanah; Ahmad Zainuri; Muslim Gani Yasir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of a love-based curriculum in realizing humanistic and civilized education at MTsN 2 Empat Lawang. This research is motivated by the importance of education that not only focuses on cognitive aspects but also emphasizes character building, empathy, and moral values among students. This study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, students, and parents as research informants. The findings reveal that the love-based curriculum is implemented through humanistic learning interactions, empathetic communication, and persuasive as well as educative disciplinary approaches. The values of care and respect for students are reflected in the harmonious relationships between teachers and students, as well as in the school culture that upholds ethics and mutual respect. This implementation has a positive impact on students’ character development, including increased respect for others, social awareness, and responsible behavior. In conclusion, the love-based curriculum significantly contributes to the realization of humanistic and civilized education. This approach not only enhances the quality of the learning process but also fosters students to become individuals with strong character, noble morals, and good social awareness.